Pola Perencanaan dan Pengembangan Visi Pesantren: Studi Kasus di Pondok Pesantren Darussalam Ngesong Jombang - Djamaluddin Perawironegoro (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
Pesantren is an Islamic educational institution that excels in Islamic learning and education. However, these advantages do not lead to the life endurance of the pesantren, especially after the death of the founder. The orientation shift from the management based on the founder of Pesantren to a systemic approach pesantren management requires a comprehensive planning. This research was conducted to describe and analyze the pesantren’s planning pattern and the factors influencing the development of pesantren. This study employed a descriptive qualitative approach. The source of the data were Kiai, teachers, and the board of Pesantren. Data was collected through observations and in-depth interviews. The results showed that the pesanteren’s planning was carried out through several stages i.e., vision formulation, human resource preparation, vision operationalization, program implementation, and supervision. While the factors that inlfuenced the pesantren’s vision development are internal factor i.e., the leadership and management of the pesantren, and external factor i.e., government and society.